Effect of Innoprovet Probiotics on the Organism of Chickens Vaccinated Against Infectious Bronchitis - K., Ubaydullaev T.; U., Murodov X.; N., Akhmedov B. (American Journal of Biology and Natural Sciences, 2026)
This article presents data on the study of effective immunoprophylaxis against Infectious Bronchitis in Lohmann Brown breed chicks raised in industrialized poultry farms and smallholder farming operations, through the application of the "Nobilis Ma5 + Nobilis 4/91" Infectious Bronchitis vaccine in combination with the Innoprovet probiotic. Blood samples were collected from all chicks at 7 and 14 days following vaccination and Innoprovet administration, and their immune status was assessed using the Hemagglutination Inhibition (HI) test. A significant increase in antihemagglutinin (antibody) titers was detected in the experimental groups compared to the control group. The stable and elevated maintenance of antibody titers on day 14 of the study indicated the formation of a strong and long-lasting immune response in the chicks. Furthermore, live weight gain in the experimental group was consistently higher than that recorded in the control group.